2020
DOI: 10.3390/nu12113304
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 (GLP-1) in the Integration of Neural and Endocrine Responses to Stress

Abstract: Glucagon like-peptide 1 (GLP-1) within the brain is produced by a population of preproglucagon neurons located in the caudal nucleus of the solitary tract. These neurons project to the hypothalamus and another forebrain, hindbrain, and mesolimbic brain areas control the autonomic function, feeding, and the motivation to feed or regulate the stress response and the hypothalamic-pituitary-adrenal axis. GLP-1 receptor (GLP-1R) controls both food intake and feeding behavior (hunger-driven feeding, the hedonic valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 293 publications
(520 reference statements)
0
38
0
Order By: Relevance
“…Only 1015% of GLP-1 enters the systemic circulation. GLP-1 is also secreted as a neurotransmitter from neurons in the brainstem that project in areas related to the regulation of energy homeostasis [ 6 ].…”
Section: Incretin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1015% of GLP-1 enters the systemic circulation. GLP-1 is also secreted as a neurotransmitter from neurons in the brainstem that project in areas related to the regulation of energy homeostasis [ 6 ].…”
Section: Incretin Systemmentioning
confidence: 99%
“…They are also located on the nodular ganglion of the vagal nerve, whose central branches terminate in the solitary nucleus in the brainstem. Information from the nucleus is transmitted to the hypothalamus, thalamus, and hemispheres [ 6 , 9 ].…”
Section: Incretin Systemmentioning
confidence: 99%
“…CONV-R mice exhibit decreased expression of the anorexigenic neuropeptides glucagon-like peptide-1 (Glp-1) and Bdnf in the brainstem compared with GF mice (47). Since preproglucagon neurons in the NTS are the main source of GLP-1 in the brain (62,63), this suggests that the gut microbiota modulates NTS function. Expression of c-Fos in the NTS can be induced by peripheral administration of the bacterial cell wall component lipopolysaccharide (LPS) (64) and decreased by oral butyrate administration (57), both of which are associated with reduced food intake.…”
Section: Gut Microbiota and Homeostatic Feeding Controlsmentioning
confidence: 99%
“…It was for a long time postulated that the release of GLP-1 from NTS neurons is triggered by its peripheral secretion via vagal afferent signals resulting from stimulation of GLP-1R located in the vagus nerve, however recent report shown that PPG expressing neurons possess a very limited neuroanatomical connection with GLP-1R expressing vagal neurons, instead receiving input mostly from neurons, which express oxytocin receptor (OXTR), thus suggesting that central and peripheral GLP-1 signaling may facilitate its anorexygenic effects via two independent circuits [ 52 ]. Although the main central role of GLP-1 consists of the regulation of feeding behavior, studies conducted over the years elucidated more complex functions of GLP-1 in the brain, including the involvement in regulation of endocrine function including stress response, by stimulating hypothalamic neuroendocrine neurons in the PVN [ 53 ].…”
Section: Glucoregulatory Hormones Affect Energy Homeostasis and Mitochondrial Function In The Brainmentioning
confidence: 99%